(untitled) (Revista de Psicología, 2020)
This study aims to describe the relationship among the memory of historical events and characters and the Peruvian national identity by comparing responses obtained from cadets from a naval school (n=113), cadets from a military school (n= 118) and students from a private university in Lima (n= 115). The results show a more positive evaluation of the history and greater levels of identification with Peru in cadets of both military educational institutions, compared to university students. These findings suggest the relevance of historical narratives transmitted in academically forming institutions as sources of storytelling biases according with military or civic traditions, and how these representations are related to national identity.